The China–Pakistan Economic Corridor (CPEC): challenges and prospects. Issue 4 (2nd October 2019) - Khan, Shehryar; Liu, Guijian
ABSTRACT: The China–Pakistan Economic Corridor (CPEC) is a US$62 billion project designed to resolve Pakistan's energy deficit, improve connectivity, and establish economic development zones and supporting social infrastructure that lay the foundations for subsequent economic growth, grapple with endemic instability and exploit Pakistan's strategic position. Challenges posed by the geographical environment, terror groups, political instability and the management of debt, along with geopolitical issues relating especially to relationships with India, are examined and assessed.